Opportunities and obstacles to the elimination of malaria from Peninsular Malaysia: knowledge, attitudes and practices on malaria among aboriginal and rural communities - Al-Adhroey, A.H.; Nor, Z.M.; Al-Mekhlafi, H.M.; Mahmud, R. (2010)
Background: Despite continuous efforts by the government and private sectors, malaria is still a public health problem in rural Peninsular Malaysia. This study investigated household knowledge, attitude and practices (KAP) regarding malaria in two malaria endemic communities, forest-aboriginal and rural communities, in the Lipis district of Pahang state, Malaysia. Methods: A descriptive cross-sectional study with a semi-structured questionnaire was carried out among 100 and 123 households from forest-aboriginal and rural areas, respectively. Results: Knowledge about malaria and its transmission is significantly higher among the rural participants than the aborigines (86.2 vs 76, p < 0.01). However, use of medicinal plants and beliefs in witchcraft and sorcery in treating febrile diseases were significantly higher among the aboriginal population (p < 0.01). There were no significant differences between the two communities in terms of the knowledge about malaria symptoms, attitudes towards its severity and practices in preventive measures against malaria by using mosquito bed nets. However, the knowledge and practice of different preventive measures to combat malaria, such as insecticide and the elimination of breeding areas, was significantly higher among the rural population than the aborigines (p < 0.001). Conclusions: Both communities were aware of malaria as a disease, but knowledge, attitudes and practices were inadequate. Providing efficient health education to people residing in malaria endemic areas would improve their understanding about malaria prevention in order to bring about the elimination of malaria from the country.